Congenital Zika Virus Infection Impairs Corpus Callosum Development - Raissa Rilo Christoff; Jefferson H. Quintanilha; Raiane Oliveira Ferreira; Jessica C. C. G. Ferreira; Daniel Menezes Guimarães; Bruna Valério-Gomes; Luiza M. Higa; Átila D. Rossi; Maria Bellio; Amilcar Tanuri; Roberto Lent; Patricia Pestana Garcez (Viruses, 2023)
Congenital Zika syndrome (CZS) is a set of birth defects caused by Zika virus (ZIKV) infection during pregnancy. Microcephaly is its main feature, but other brain abnormalities are found in CZS patients, such as ventriculomegaly, brain calcifications, and dysgenesis of the corpus callosum. Many studies have focused on microcephaly, but it remains unknown how ZIKV infection leads to callosal malformation. To tackle this issue, we infected mouse embryos in utero with a Brazilian ZIKV isolate and found that they were born with a reduction in callosal area and density of callosal neurons. ZIKV infection also causes a density reduction in PH3+ cells, intermediate progenitor cells, and SATB2+ neurons. Moreover, axonal tracing revealed that callosal axons are reduced and misrouted. Also, ZIKV-infected cultures show a reduction in callosal axon length. GFAP labeling showed that an in utero infection compromises glial cells responsible for midline axon guidance. In sum, we showed that ZIKV infection impairs critical steps of corpus callosum formation by disrupting not only neurogenesis, but also axon guidance and growth across the midline.